First Report of Geotrichum candidum from Pakistan Causing Postharvest Sour Rot in Loquat (Eriobotrya japonica) - R. Hafeez; N. Akhtar; A. Shoaib; U. Bashir; M. S. Haider; Z. A. Awan (Journal of Animal and Plant Sciences, 2015)
Post-harvest diseases of fruits are the major threat to fruit quality and cause heavy economic losses. During a survey of the local fruit market in Lahore in the summer of 2014, several samples of rotted loquat fruits were collected to identify the causal organism. Geotrichum candidum (FCBP1335) was isolated, purified and identified initially on the basis of morphological characteristics. Further confirmation of identified fungus was carried out by sequencing the Amplified Internal Transcribed Spacer (ITS) sequence (ITS1-5.8S rDNA-ITS4 region) from total genomic DNA of the isolated causal fungus. Re-isolation of same fungal pathogen from the artificially innoculated loquat fruits fulfilled the Koch’s postulates. To our knowledge, G. candidum is reported for the first time, causing rotting in loquat fruit not only from Pakistan but also from the world. Present investigation will be very helpful for management of this post-harvest disease.
Keywords: Loquat; sour rot; Geotrichum candidum; Pakistan